2021
DOI: 10.1159/000515161
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Prognostic Index Predicts Clinical Outcome and Mortality in Hospitalised Older Patients with Diverticular Disease

Abstract: <b><i>Introduction:</i></b> The Multidimensional Prognostic Index (MPI) is a validated tool for assessing mortality risk in hospitalised patients. We aimed to evaluate whether the MPI predicted mortality and the risk of developing diverticular disease (DD) complications in older patients. <b><i>Methods:</i></b> This is a multicentre study conducted in January 2016-March 2018. All patients with DD aged 65 years and older were included. Patients were stratified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous studies have reported a significant association between MPI and negative outcomes (in particular mortality) in hospitalized older patients affected by several independent medical conditions [ 30 – 35 ]. However, more recent studies have shown that slightly modified versions of the MPI can predict negative outcomes in community-dwelling older people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a significant association between MPI and negative outcomes (in particular mortality) in hospitalized older patients affected by several independent medical conditions [ 30 – 35 ]. However, more recent studies have shown that slightly modified versions of the MPI can predict negative outcomes in community-dwelling older people.…”
Section: Discussionmentioning
confidence: 99%